TEACHERS' CREATIVE THINKING TENDENCIES AND THEIR CREATIVITY-FOSTERING CLASSROOM PRACTICES IN STEM EDUCATION - Aslan, Beyzanur; Ince, Murat (SCIENTIA SOCIALIS, 2025)
This study examined the link between teachers'creative thinking tendencies and their creativity-fostering classroom practices in the context of STEM education. Employing a correlational research design, data were collected from 338 in-service teachers actively integrating STEM approaches into their instruction. Two standardized instruments were used: the Marmara Creative Thinking Tendencies Scale and the Creativity-Fostering Teacher Behavior Index. Descriptive statistics and inferential analyses (t-tests and one-way ANOVA) were conducted to examine group differences based on gender, subject area, and participation in training programs. Findings revealed no significant gender or subject-area differences in creative thinking tendencies; however, teachers who had participated in multiple training programs exhibited significantly higher scores. In contrast, female teachers demonstrated significantly higher creativity-fostering behaviors than male teachers, and preschool teachers outperformed ICT teachers in these behaviors. No significant differences were found regarding participation in STEM training programs and creativity-fostering behaviors. The findings underscore the nuanced role of teacher characteristics in promoting creativity within STEM education and suggest implications for professional development and educational design.
Keywords: STEM education; creative thinking; creativity-fostering behaviors; teacher characteristics; professional development; INTELLIGENCE; Education & Educational Research